The Model for End-Stage Liver Disease (MELD) can predict outcomes in ambulatory patients with advanced heart failure who have been referred for cardiac transplantation evaluation - Szyguła-Jurkiewicz, Bożena; Zakliczyński, Michał; Andrejczuk, Mariusz; Mościński, Mateusz; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Risk stratification in heart failure (HF) patients is an important element for management. There are several risk stratification models that can be used to predict the prognosis of patients with HF, such as Aaronson’s scale, CVM-HF (CardioVascular Medicine Heart Failure), the Seattle Heart Failure Model (SHFM) and the Munich score. These models fail to adequately address the impact of multiorgan dysfunction on prognosis. The classical Model for End-Stage Liver Disease (MELD) score consists of: total bilirubin, INR (international normalized ratio) and creatinine level. There are some modifications of the MELD scale: MELD-XI, which excludes the INR score; the modMELD score, in which INR is replaced with albumin levels; and MELD-Na, which consists of the bilirubin and creatinine levels, INR ratio and the sodium level. Therefore, the MELD score systems are markers of multisystem dysfunction (renal, cardiac, hepatic). It is important that they are composed of routinely collected laboratory measures which are easy to use.